Strengthening Cross-Border Ties: A Participatory Vision for EuroGuadiana Tourism - Thomas Panagopoulos; Pooyan Sedarati; Joaquim Pinto Contreiras (Journal of Tourism, Sustainability and Well-being)
This article delves into the intricacies of Eurocity of Guadiana (EuroGuadiana) cross-border initiative that seeks to bolster economic value through innovative tourism products. It delineates a comprehensive plan aimed at turning EuroGuadiana into a center of cultural and economic vibrancy within Andalusia/Algarve, thus overturning its current peripheral status, using a rich body of literature on regional development and tourism strategies. The key to this strategy is a meticulous tourism diagnosis, facilitated by a value chain tool that identifies existing resources and their potential for complementarity and cooperation, aligning strategic decisions with the factors that increase potential tourists’ perceptions. Participatory methods and transborder community development are key components of the strategy. The former encourages inclusivity and collaboration, integrating diverse stakeholder insights into the decision-making process, thereby fostering a strategy that is both grounded and adaptive to the evolving preferences of tourists. The latter leverages the region’s unique cross-border position to build cultural cohesion and economic synergy, promoting collaborative efforts in conservation and sustainable practices. Envisioned as a beacon of sustainable and inclusive development, EuroGuadiana aspires to emerge as a destination characterized by diversity, prosperity, and vibrancy. Furthermore, it aims to establish a collaborative platform that bridges cities within the region, fostering a network that is conducive to shared growth and innovation. With this multi-faceted approach, EuroGuadiana is being repositioned as a dynamic and harmonious hub of regional development.